Defense protocol [large type] - Andrews, Brian, 1973-; Wilson, Jeff, 1963-; Clancy, Tom, 1947-2013 (Clancy, Tom, 1947-2013. Jack Ryan novel, 2024)
For decades, Taiwan has been a thorn in the side of the Chinese government. New Chinese President Li Jian Jun has devised a secret military operation to take the island. Meanwhile, Lt. Commander Katie Ryan is deployed on the USS Jason Dunham to defend Taiwan and under pressure to find a flaw in the invaders' plan for her father to exploit. For his part, President Jack Ryan may have the power of the entire US military at his disposal, but what he really needs are Li's secret plans so he can stave off a war. Because America's Defense Protocol could lead to a game of mutual destruction that could cost the lives of thousands.--